Quantification of seasonal training-load in elite English Premier League soccer players - Kelly, D. M. (John Moores University, 2020)
To date, limited data exists regarding the seasonal training-loads incurred by elite soccer players. The purpose of the thesis was to examine the seasonal training-load incurred by elite English Premier League soccer players including the influence of different coaching philosophies on player loading and resulting player training status. The aim of the first study (Chapter 4) was to compare two different tools used for measuring internal training load in elite English Premier League soccer players. During an in-season competitive period, the field-based training sessions of 19 elite players were monitored across a total of 1010 individual sessions. Players were also categorised in relation to playing position, with 4 central defenders, 4 wide defenders, 6 central midfielders, 2 wide midfielders, and 3 attackers participating in the study. The correlation between changes in sRPE and heart rates was r = 0.75 (95% CI: 0.71-0.78), with correlations remaining high across the different player positions (wide-defender, r = 0.81; central-defender, r = 0.74; wide midfielder, r = 0.70; central midfielder, r = 0.70; attacker, r = 0.84; P < 0.001). The correlation between changes in sRPE and HR, measured during a season-long period of field-based training, is high in a sample of elite soccer players. The aim of the second study (Chapter 5) was to quantify the seasonal training loads elicited in elite English Premier League soccer players. External (global positioning system [GPS]) and internal (sRPE-TL) training loads were analysed in 26 elite soccer players across an in-season (36-week) competition phase. A stadium-based tracking system was used to record external load during 49 matches. Training and match loads were categorised into 6-week mesocycle phases, and subsequent weekly (microcycle) calendar blocks. Players were assigned according to playing position, with 4 central defenders, 4 wide defenders, 7 central midfielders, 3 wide midfielders, and 8 attackers participating in the study. Daily sRPE-TL (95% CI range, 15 to 111 AU) and total distance (95% CI range, 179 to 949 m) were higher during the early stages (mesocycle 1 and 2) of the competition period. Across the within-week microcycles, load was greater on match day and lowest pre-match day (G-1) vs. all other days, respectively (p < 0.001). sRPE-TL (~70-90 AU per day) and total distance (~700-800 m [per day]) progressively declined over the 3-days leading into a match (p < 0.001). High-speed distance was greater 3-days (G-3) before a game vs. G-1 (95% CI, 140 to 336 m) while very high-speed distance was greater on G-3 and G-2 than G-1 (95% CI range, 8 to 62 m; p < 0.001). This was the first study to systematically quantify the training and match loads employed by an English Premier League team across a competitive season. The observed training and match load indicated that periodisation of training is mainly evident across the weekly microcycle, particularly during the 3-days leading into competition. The periodisation strategy adopted during the competition period, largely reflects the head coach's personal philosophy, and attempts to balance the need to ensure adequate post-match recovery with optimal preparation for the subsequent game. The aim of the third study (Chapter 6) was to evaluate the training load distribution in elite English Premier League soccer players under two different coaching strategies. The 20 elite soccer players were monitored across the annual competition phase (36-week) of two successive seasons (2012-2013 [season 1]; 2013-2014 [season 2]). Training load was categorised into 6-week mesocycle phases, and subsequent weekly (microcycle) calendar blocks. There was a significant interaction between season and mesocycle for all variables (all p < 0.05). Mean match high-speed distance covered was 159 ± 79 m higher in season 1 (2334 ± 961 m) compared with season 2 (2175 ± 907 m) (95% CI range, 57 to 261 m) (p < 0.05). There was a higher frequency of competitive matches in season 1 (n = 49) than season 2 (n = 34). Daily training minutes were higher across mesocycles 1 and 2 in season 1 versus season 2 (95% CI range, 1.2 to 13.6 min). In contrast, all other variables (sRPE-TL, total distance, high-speed distance, very high-speed distance, accelerations, decelerations) were greater in season 2 than season 1 across selected mesocycles. There was a statistically significant interaction between season and day type for all variables (all p < 0.001). Daily training minutes were higher on G-3 (95% CI range, 6.0 to 12.8 min) in season 1 versus season 2. s-RPE-TL, total distance, high-speed distance, and very high-speed distance were all greater during season 2 compared with season 1 (all p < 0.001). A higher number of accelerations were observed across all day types (95% CI range, 13 to 30 [n]), and a greater frequency of decelerations were reported on G-3, G-2, and G-1 in season 2 compared with season 1 (95% CI range, 18 - 35 [n]). The present findings indicate novel insights into how different periodisation strategies adopted by coaches impact the training loads elicited in a sample of elite soccer players. This was the first study to systematically evaluate the influence of different coaching philosophies in the same group of elite players at an English Premier League club. The aims of the fourth and final study (Chapter 7) was to determine the ASRM responses in elite English Premier League soccer players under two different coaching strategies (Chapter 6). Daily ASRM (fatigue, sleep quality, and muscle soreness [DOMS]) were measured in the same 20 elite soccer players using a 7-point Likert psychometric questionnaire (Hooper et al., 1995). ASRM were taken from each player across the three training days leading into competition (G-3, G-2, and G-1). Mean differences in ARSM between mesocycles and day-type were assessed for practical relevance against a minimal practically important difference (MPID) of 1-point on the 7-point Likert scale. Match load covariate adjusted mean wellness measures were significantly higher during season 2 compared with season 1 (p < 0.05). Despite the observed statistically significant differences for mean daily fatigue (95% CI range, -0.2 to 0.2 AU), sleep (95% CI range, -0.1 to 0.1 AU), and muscle soreness (95% CI range, -0.04 to 0.04 AU), no MPID were observed between season 1 and season 2. The present findings demonstrate that differences in training load across the three days leading into a game did not elicit practically relevant changes (> 1-point) in the ASRM response when controlled for differences in match load. These findings have important implications for the application of ASRM across in-season training weeks in elite soccer. Future research is needed to examine the responsiveness of ASRM to changes in training and competition loads in elite players. The results of this thesis provide novel information regarding the evaluation of training load in elite soccer players. The data demonstrate that sRPE is a valid, simple and non-invasive measurement tool for assessing the internal load in soccer players while data describing training periodisation philosophies adopted by elite teams provides valuable insights for physical coaches preparing elite players. Finally, information presented on ARSM provides practitioners with important insights regarding their implementation across the weekly training microcycle undertaken by elite players.